25 rocznica walki o krzyże w Nowej Hucie [blok znaczków podziemnych] . 25th anniversary of the struggle for the cross in Nowa Huta. Sheet of unofficial stamps - Poczta Solidarności. (Poczta Solidarności, 1985)
Blue print on white paper, without perforation. Sheet, with "Poczta Solidarności" imprint, released on the 25 anniversary of the conflict around erection of a church in Nowa Huta, includes 4 stamps, which represent scenes (mass protests), symbols (the cross) and institutions (Nowa Huta Cross editorial house) related to the event. Price: 50 zł per stamp.